BIMBINGAN MANASIK HAJI KOTA SURAKARTA TERHADAP AKHLAKUL HAJ DAN ADAT ISTIADAT ORANG ARAB - Syamsuddin, S; Abbas, Ngatmin; Isfihani, I; Mujiburrohman, M; Rochmawan, Alfian Eko (AL HAZIQ: Journal of Community Service, 2024)
The background of this community service is the increasing need for Hajj pilgrims to deeply understand the proper procedures of Hajj and the ethical conduct during the pilgrimage (akhlakul haj), especially when facing cultural and physical challenges in Saudi Arabia. Many pilgrims have limited knowledge about the rituals and feel anxious about adapting to the local culture. Therefore, this Hajj guidance program was designed to provide both theoretical and practical understanding of the proper Hajj rituals and the ethical behavior to maintain during the pilgrimage. The main objective of this program is to enhance the pilgrims' readiness in terms of technical, mental, and spiritual aspects, while equipping them with the ability to adapt to the Arab customs. The methods employed include delivering theoretical materials on Hajj, interactive discussions, practical Hajj simulations, and evaluation and reflection sessions. The results of this community service show a significant increase in the participants' understanding, both technically and spiritually. Participants became more prepared physically and mentally to perform Hajj after the practical simulations, and they also gained a deeper understanding of the importance of maintaining ethical conduct and interacting respectfully with the local community in Saudi Arabia. This program successfully provided pilgrims with adequate preparation for the profound spiritual journey in the Holy Land.